VEMP Cervical e Ocular como Teste Diagnóstico da Deiscência do Canal Semicircular Superior - Valente, Maria Clara Motta Barbosa; Carnaúba, Aline Tenório Lins; Menezes, Pedro de Lemos; Di Cavalcanti, Maria Eduarda (Distúrbios da Comunicação, 2017)
Hunter JB, Patel NS, O’Connell BP, et al. Cervical and Ocular VEMP Testing Diagnosing Superior Semicircular Canal Dehiscence. Otolaryngol Head Neck Surg. 2017; p. 1-7.